The Implementation of Competency Certification Test for Vocational Students of Light Vehicle Engineering Program by LSP-P3 in Banyumas - Kuntoro, Tri; Sudana, I Made; Anis, Samsudin (Universitas Negeri Semarang, 2019)
The aim of this study was to implement the competency certification test for vocational students of light vehicle engineering program by LSP-P3 in Banyumas, which covers aspects of context, input, process, product and thoroughly. This research was conducted in four vocational schools in Banyumas. The population was 16 assessors. All member of the population was used as the sample of this research. The instrument used a questionnaire. The validity test with the content validity of the CVR (content validity ratio), the validity of items with a limited test and product moment analysis was performed. Cronbach alpa was used as the reliability test of this research. The data analysis techniques used a descriptive analysis. The description of the data used a level category approach. The results showed that the implementation of competency certification test for vocational students of light vehicle engineering program by LSP-P3 in Banyumas evaluated from the aspects of: (1) context included in the excellent category with a quality achievement score of 41.63 or (86.7%) ; (2) input included in the excellent category with a quality achievement score of 55.18 or (86.23%); (3) process included in the excellent category with a quality achievement score of 37.50 or (85.23%); (4) product included in the excellent category with a quality achievement score of 27.44 or (85.74%); and (5) as a whole included in the excellent category with a value of achievement quality results of 161.75 or (86.04%). The implementation of competency certification test for vocational students of light vehicle engineering by the LSP-P3 in Banyumas needs to be improved optimally although it has been going very well. This implies that the implementation of the competency certification test must consider the competency of the assessor. The implementation of competency certification test should use equipment that is in line with current technological developments. The competency certification test should be carried out in stages to complete the whole scheme so that graduates get a level 2 SKKNI competency certificate.